Iconoclasm, identity politics and the erasure of history - Adams, Alexander 1973- (Societas, 2020)
Iconoclasm, Identity Politics and the Erasure of History surveys the origins, uses and manifestations of iconoclasm in history, art and public culture. It examines the various causes and uses of image/property defacement as a tool of political, national, religious and artistic process. This is one of the first books to examine the outbreak of iconoclasm in Europe and North America in the summer of 2020 in the context of previous outbreaks, and it examines the implications of iconoclasm as a form of control, censorship and expression.